ANALISIS PENDAPATAN USAHA PENANGKARAN BENIH PADI DI DESA KARANG TUNGGAL KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA (Analysis of Rice Seed Breeding Business Income in Karang Tunggal Village, Tenggarong Seberang District) - SYSWY NUR BEWTY; SYARIFAH AIDA; MUHAMMAD ERWAN SURIAATMAJA (Universitas Mulawarman (University of Mulawarman), 2023)
Seed breeding is an effort to produce superior seeds. Seeds play a big role in determining the success of crop production and productivity. One of the technological innovations that are expected to be introduced to improve paddy rice cultivation is the technology of breeding high-yielding varieties of rice seeds. The purpose of this study is to determine the production costs of rice seed breeding businesses, to determine the total receipts and income received, and to analyze the feasibility of rice seed breeding businesses in the Mekar Sari Seed Breeding Group, Karang Tunggal Village, Tenggarong Seberang District, Kutai Kartanegara Regency.The study was conducted from April to June 2022. The research location was determined intentionally (purposive) in the Mekar Sari Seed Breeding Group, Karang Tunggal Village, Tenggarong Seberang District, Kutai Kartanegara Regency. The data needed in this study are primary and secondary data. The method used in sampling is a saturated sampling method or census with a total of 15 respondents. The data analysis method used is the analysis of production costs, receipts, income, and R/C Ratio.The results showed that the rice seed breeding business in Karang Tunggal Village, Tenggarong Seberang District, obtained an average production cost of Rp. 9,408,574.76 mt⁻¹ with an average per hectare of Rp. 8,846,379.29 Ha⁻¹ mt⁻¹ average receipt of Rp. 25,360,000 mt ⁻¹ with an average per hectare of Rp. 23,520,000 Ha⁻¹ mt⁻¹ and an average income of Rp. 15,951,425.24 mt⁻¹ with an average per hectare of Rp. 14,673,620.71 Ha⁻¹ mt⁻¹.The result of the R/C Ratio analysis is 2.6. The R/C Ratio value shows that the rice seed business in the Mekar Sari Group is profitable and worth working on because of the R/C Ratio > 1.